Generation of synthetic day scenarios for renewable energy production using generative adversarial networks - González Parra, Josué Daniel (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
Generative Adversarial Networks are a type of neural networks in artificial intelligence model, found in deep learning and allow generating new samples from examples. This type of neural networks can create new types of data, such as images, videos of music, so realistic that it is impossible to distinguish if the sample was entirely computer generated or was made by a person. In this thesis we answer the question if generative adversarial networks can generate daily time series as if actually happened and taking into account what is expected on that day. Each generated sample will help to anticipate the interruption on the energy due to the fluctuations of weather conditions. We will use three different time series: approximately two years of daily samples of solar irradiance and ambient temperature, and almost a year of daily data for wind speed. Each of these time series has its own features and thus we will design a different models for each model to be capable of replicate the daily patterns and disturbances. The obtained results were successful because it was possible to capture the dynamics, the function probability distribution, and the fluctuations due to the weather for each time series.

Las Redes Neuronales Generativas Adversariales (Generative Adversarial Networks, en inglés) son un tipo de redes neuronales de inteligencia artificial usadas dentro del aprendizaje profundo (Deep Learning) que permiten la generación de nuevos datos a partir de ejemplos. Este tipo de redes pueden crear nuevos tipos de datos, como imágenes, videos o música, tan reales que sea imposible de distinguir si la muestra fue creada desde cero por un algoritmo o fue generada por alguna persona. En esta tesis resolvemos si las redes generativas adversariales pueden crear series de tiempo con resolución diaria como si fueran datos reales y así poder tomar en consideración que se espera en ese día. Cada muestra generada ayudara a contemplar las interrupciones en la energía debido las intermitencias del clima. Usaremos datos de series de tiempo de: casi dos años de datos de irradiancia solar y temperatura ambiente, y casi un año de datos de velocidad de viento. Cada una de esas series tiene sus propias características y por ello creamos una red para cada una de ellas que sea capaz de modelar los patrones y perturbaciones diarias. Los resultados obtenidos fueron satisfactorios porque se logró capturar la dinámica, la función de distribución, y las fluctuaciones debido al clima, de cada serie de tiempo.
Facultad de Ingeniería Eléctrica. Maestría en Ciencias en Ingeniería Eléctrica
Keywords: info:eu-repo/classification/cti/7; FIE-M-2021-0848; Redes neuronales; Modelos generativos; GAN; Series de tiempo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6329